Nucleotide sequence of 5S rDNA and localization of the ribosomal RNA genes to metaphase chromosomes of the Tilapiine cichlid fish, Oreochromis niloticus - Martins, Cesar (2000)
In this study, we report the cloning and nucleotide sequence of PCR-generated 5S rDNA from the Tilapiine cichlid fish, Oreochromis niloticus. Two types of 5S rDNA were detected that differed by insertions and/or deletions and base substitutions within the non-transcribed spacer (NTS). Two 5S rDNA loci were observed by fluorescent in situ hybridization (FISH) in metaphase spreads of tilapia chromosomes. FISH using an 18S rDNA probe and silver nitrate sequential staining of 5S-FISH slides showed three 18S rDNA loci that are not syntenic to the 5S rDNA loci.